State of the Art—Encoding Subjective Probabilities: A Psychological and Psychometric Review - Wallsten, Thomas S.; Budescu, David V. (Management Science, 1983)
In order to review the empirical literature on subjective probability encoding from a psychological and psychometric perspective, it is first suggested that the usual encoding techniques can be regarded as instances of the general methods used to scale psychological variables. It is then shown that well-established concepts and theories from measurement and psychometric theory can provide a general framework for evaluating and assessing subjective probability encoding. The actual review of the literature distinguishes between studies conducted with nonexperts and with experts. In the former class, findings related to the reliability, internal consistency, and external validity of the judgments are critically discussed. The latter class reviews work relevant to some of these characteristics separately for several fields of expertise. In die final section of the paper the results from these two classes of studies are summarized and related to a view of vague subjective probabilities. Problems deserving additional attention and research are identified.